A Pilot study to evaluate malaria control strategies in Ogun State, Nigeria (2007)
With limited evidence of decreases in malaria-related mortality and morbidity, and nearly half the time to the 2010 deadline of Roll Back Malaria (RBM) targets now past, we conducted this study to assess the awareness, accessibility and use of malaria control strategies among at-risk groups within the context of RBM in Nigeria. It was a descriptive, cross-sectional pilot study of 34 registered women attending antenatal clinics and 34 mothers of children less than five years old, using a questionnaire in a malaria holo-endemic community of Ogun State, Nigeria. Results showed that 14.7% and 16.2% of all respondents interviewed were aware of the home management of malaria (HMM) program (17.6% of mothers of children under five years vs. 11.8%of pregnant women) and the change in policy on malaria treatment (23.5% of mothers of children under five years vs. 8.8% of pregnant women) respectively. Younger respondents knew more about HMM than older ones (p <.05). Most (63.2%) of the 68 respondents (64.7% of mothers of children under five years vs. 61.8% of pregnant women) interviewed knew about insecticide treated nets (ITNs); however, only 22.1% were using the treated material. Reasons given by those not using ITNs included: they did not know about ITN prior to the interview (43.3%), they had no money (41.5%) and they did not know where to get it (7.6%). Only 5.8% of mothers of children less than five years old, and none of the pregnant women, had taken the new combination drug. Eight (23.5%) of the 34 pregnant women interviewed knew about intermittent preventive treatment of malaria for pregnant women (lPT), while two (25.0%) of these eight women had received a preventive treatment dose. The results of this pilot study showed that efforts need be intensified to make adequate information and materials relating to the different malaria control strategies more available and accessible at the community level to achieve and sustain the RBM goals, both in Ogun State and in Nigeria in general. However, a larger study is needed to provide more generalized findings